CORPORATE GOVERNANCE AND ECONOMIC SUSTAINABILITY: INVESTIGATING THEIR INTERDEPENDENCE IN MODERN BUSINESS PRACTICES - Shaifali (International Journal of Research -GRANTHAALAYAH, 2025)
This article explores the connection between economic sustainability and corporate governance within business societies today. In a quantitative strategy, the research analyzes governance mechanisms and economic performance measures among a sample of listed companies. The results suggest that there exists a high-strength positive relationship between effective governance mechanisms and economic sustainability in the long term. The results validate the function of governance practices to make organizations economically sustainable and resilient. Implications for business leaders, policymakers, and future research are discussed.